Obtenção e caracterização de nanopartículas de argilominerais - Costa, Tharsia Cristiany de Carvalho (2009)
Natural nanoclays are of great interest particularly for the production of polymer-based nanocomposites. In this work, kaolinite clays from two natural deposits in the State of the Rio Grande do Norte and Paraiba were purified with thermal treatment and chemical treatments, and characterized. Front to the gotten data, had been proposals methodologies for elimination or reduction of coarse particle texts, oxide of iron and organic substance. These methodologies had consisted of the combination of operations with thermal treatments, carried through in electric oven, and acid chemical attacks with and hydrogen peroxide. The Analyzers Thermogravimetric was used to examine the thermal stability of the nanoclays. The analysis indicated weight losses at temperatures under 110 ºC and over the temperature range of 350 to 550 ºC. Based on the thermal analysis data, the samples were submitted to a thermal treatment at 500 °C, for 8 h, to remove organic components. The X-ray diffraction patterns indicated that thermal treatment under 500 °C affect the basic structure of kaolinite. The BET surface area measurements ranged from 32 to 38 m2/g for clay samples with thermal treatment and from 36 to 53 m2/g for chemically treated samples. Thus, although the thermal treatment increased the surface area, through the removal of organic components, the effect was not significant and chemical treatment is more efficient, not affect the basic structure of kaolinite, to improve particle dispersion. SEM analysis confirms that the clay is agglomerated forming micron-size particles